Understanding capitalism: critical analysis from Karl Marx to Amartya Sen / edited by Douglas Dowd - "Dowd, Douglas (ed.)" (London, 2002)
Understanding Capitalism combines the essays of seven leading economists, including Robin Hahnel and John Bellamy Foster, in a critical assessment of the relationship between economic thought and the dominance of capitalism. With analyses of economists ranging from Karl Marx to Amartya Sen, the book traces the growth of the capitalist system over the past two hundred years and how economic theory has, in fact, become capitalist ideology. Relating socio-economic and analytical histories to present-day economic policy, this is a thoroughly accessible work which makes an ideal introduction to the key thinkers in economic thought past and present.Major economists and economic schools of thought are discussed in a chapter-by-chapter guide that covers Marx, Veblen, Gramsci, post-Keynesian theory, US institutionalists, Sweezy and the Monopoly Capital school, and recent Nobel Prize winner Amartya Sen. Contributors include Michael Lebowitz, Carl Boggs, Michael Keaney, Frederic Lee, John Bellamy Foster and Robin Hahnel, with an introduction by the editor, Douglas Dowd.
Keywords: Capitalism-History